2019
DOI: 10.1182/blood-2019-131014
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Dosing of CLR 131 in Patients with Relapsed or Refractory Multiple Myeloma (RRMM)

Abstract: Background: CLR 131 is a novel targeted radiotherapeutic that exploits the selective uptake and retention of phospholipid ethers (PLEs) by malignant cells. Based on initial preclinical and clinical experience and the radiosensitivity of MM, fractionated dosing of CLR 131 is being examined in RRMM in a Phase 1 trial (NCT02278315) and a Phase 2 trial, CLOVER-1 (NCT02952508). Methods: Both the Phase 1 and Phase 2 trials of CLR 131 aim to determine efficacy and safety in RRMM. Eligibility criteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Initial findings from this CLOVER-1 expansion cohort of quad-class refractory (including anti-BCMA immunotherapy) R/RMM patients adds to the body of evidence that fractionated dosing achieving ≥60 mCi total body dose of iopofosine can be safely administered, leading to an ORR of 50%, with stable disease or better for all treated patients. The depth and durability of response to iopofosine in this heavily pretreated, refractory population compares favorably with previous experience with iopofosine [ 8 , 9 ] and other treatments being used alone in similar patient populations [ 11 13 ]. One limitation of this primary analysis was its small patient cohort and the short duration of follow-up.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Initial findings from this CLOVER-1 expansion cohort of quad-class refractory (including anti-BCMA immunotherapy) R/RMM patients adds to the body of evidence that fractionated dosing achieving ≥60 mCi total body dose of iopofosine can be safely administered, leading to an ORR of 50%, with stable disease or better for all treated patients. The depth and durability of response to iopofosine in this heavily pretreated, refractory population compares favorably with previous experience with iopofosine [ 8 , 9 ] and other treatments being used alone in similar patient populations [ 11 13 ]. One limitation of this primary analysis was its small patient cohort and the short duration of follow-up.…”
supporting
confidence: 64%
“…Additionally, the PLE portion of the molecule inhibits AKT. Phase I trials with iopofosine in patients with advanced solid tumors or highly pretreated R/RMM have shown that iopofosine can be safely administered intravenously and elicits a deep and durable response in highly pretreated populations [ 8 , 9 ]. In patients with triple-class refractory R/RMM receiving a total dose of >60 mCi, an overall response rate (ORR) of 40% and PFS of >3 months have been observed in early trials.…”
mentioning
confidence: 99%
“…29 First generation 131 I-NM404 is currently being investigated as a treatment for metastatic multiple myeloma and other cancers. [30][31][32][33] We have recently focused on evaluating the second generation APC, NM600, which can be radiolabeled with a variety of radiometals. By labeling with 86 Y, we can image tumors and perform dosimetry estimation via PET/CT, while by labeling with the isotopic pair, 90 Y, we are able to deliver therapeutic radiation.…”
Section: Open Accessmentioning
confidence: 99%